Characterisation of sea ice algal communities in the Hudson Bay (Southampton Island) - Martin Graeve; Eva Leu; Kirsten Fahl; Karley Campbell; Thomas A Brown; Nahid Welteke; Valeria Adrian-Schütte (PANGAEA, 2025)
A spring bloom of algae in or underneath sea ice provides a concentrated food source for aquatic grazers and contributes significantly to marine primary production in many regions of the Arctic. Various types of trophic markers are commonly used to analyze food web structure, based on numerous assumptions about how sea ice algae differ biochemically from phytoplankton. Changes associated with polar amplification of global warming have the potential to affect the phenology, taxonomic composition, productivity, and nutritional value of sea ice algal blooms, which are usually dominated by diatom species. Such changes are likely to have far-reaching effects on trophic interactions and carbon cycling in the ocean. The production of lipids and stable isotope biomarkers by marine algae can vary significantly depending on environmental factors such as snow depth, ice thickness, nutrient availability, and water depth. For example, concentrations of polyunsaturated fatty acids (PUFAs) in ice algae decreased with decreasing nutrient concentrations, and 16:0/16:1 (n-7) fatty acids were highly enriched in 13C in our 2019 study in northwestern Hudson Bay, Southampton Island (possibly as a result of DIC limitation). Data on stable isotope values of fatty acids in ice algae are particularly scarce, so we provide an important information base for future Bayesian isotope mixing models.